The book of Psalms - Declaissé-Walford, Nancy L.; Jacobson, Rolf A. 1965-; Tanner, Beth LaNeel (The New International commentary on the Old Testament, 2014)
Reflecting the combined insights and strengths of three superior biblical scholars, this book is the most complete and detailed one-volume commentary available on the Psalms. Nancy deClaisse-Walford, Rolf Jacobson, and Beth LaNeel Tanner offer a succinct introduction to the Psalter, a new translation of all the psalms that takes special account of the Dead Sea Scrolls, and individual entries on each psalm unit. Throughout their commentary they drew on state-of-the-art research on the canonical shape and shaping of the Psalter and give nuanced attention to the poetic nature of the psalms